2018
DOI: 10.1038/s41598-018-23830-4
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pseudohinzii targets cilia and impairs tracheal cilia-driven transport in naturally acquired infection in mice

Abstract: Several species of the Gram-negative genus Bordetella are the cause of respiratory infections in mammals and birds, including whooping cough (pertussis) in humans. Very recently, a novel atypical species, Bordetella pseudohinzii, was isolated from laboratory mice. These mice presented no obvious clinical symptoms but elevated numbers of neutrophils in bronchoalveolar lavage fluid and inflammatory signs in histopathology. We noted that this species can occur at high prevalence in a mouse facility despite regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
(57 reference statements)
2
17
0
Order By: Relevance
“…The bacteria could also be detected in the nasal swabs and lung on days 12 PI, as well as in the trachea and cecal contents. The replication of B. pseudohinzii in trachea and lung of the mice has been demonstrated in previous studies . Our novel finding in the present study was that the infected mice shed the bacteria in their feces which contaminated the cage padding.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The bacteria could also be detected in the nasal swabs and lung on days 12 PI, as well as in the trachea and cecal contents. The replication of B. pseudohinzii in trachea and lung of the mice has been demonstrated in previous studies . Our novel finding in the present study was that the infected mice shed the bacteria in their feces which contaminated the cage padding.…”
Section: Resultssupporting
confidence: 71%
“…The 16S rRNA gene was amplified using universal primers (forward primer: 5'‐AGAGTTTGATCMTGGCTCAG‐3', reverse primer: 5'‐TACGGYTACCTTGTTACGACTT‐3'). The partial B. pseudohinzii outer membrane protein A (OmpA) gene was amplified using primer pairs as previously described . All the primers were synthesized by Sangon Biotech.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Bph persists in the respiratory tract of mice for months after inoculation ( Dewan et al, 2019 ), the preponderance of infections do not lead to overt signs of illness ( Hayashimoto et al, 2012 ). Others have reported that despite its apparent benign effects on mice, Bph can induce changes in pulmonary immune parameters (e.g., neutrophilia), leading to concerns about Bph possibly confounding murine pulmonary disease models ( Clark et al, 2016 , 2017 ; Perniss et al, 2018 ). On the other hand, we speculated that studying a bacterium within the context of AAI that evolved to reside in the murine respiratory tract and was not transplanted from humans may provide unique insights into how prolonged exposure to a respiratory microbe affects pulmonary inflammation.…”
Section: Introductionmentioning
confidence: 99%